A Discussion of the Decision to Apply Interim Measures of Emergency Arbitration - Le Nguyen Gia, Thien (VNU Journal of Science: Legal Studies; Vol 38 No 4, 2022)
The emergency arbitration clause has been added to the arbitration rules of several arbitration centers around the world. The emergency arbitration shall be appointed before the establishment of the arbitral tribunal and shall be tasked with issuing interim measures. If there is no emergency arbitration, a party needs to wait until the arbitral tribunal is formally formed or ask the court to issue measures. If parties have to wait until the arbitral tribunal is formed, then the enacted interim measures are too late and therefore ineffective. Thus, with its characteristics, the emergency arbitrator has overcome this situation and demonstrated the importance of protecting the assets and legitimate interests of the parties. Emergency arbitration is still a new matter in Vietnam. This article focuses on a detailed analysis of some theoretical and practical issues of emergency arbitration in international arbitration. The article then concludes by proposing suggestions about the ability to enforce emergency arbitration decisions in international arbitration laws.